Triumph of the light—isopathy and the rise of transcendental homeopathy, 1830–1920. Issue 1 (1st June 2003) - Morrell, P
Abstract : Modern homeopathy dwells in a nebulous and metaphysical realm into which few non-homeopathic doctors would venture; a very different world and speaking a language virtually incomprehensible to science. Fundamentally incompatible systems, their highly sophisticated conceptions of "disease" and "cure" are sufficiently divergent to prevent their peaceful coexistence. Can the best of modern scientific medicine be reconciled with this recently resuscitated "medical Lazarus"? Could a creative dialogue be established? This article explores the development of modern homeopathic thinking between 1830 and 1920, charting a discourse within homeopathy initiated in the 1830s with reference to use of "higher potencies" and disease products ("nosodes"). Incorporation of disease products into the homeopathic mainstream killed off and supplanted the earlier allopathic version of homeopathy, encouraged the use of higher potencies, and legitimated a widespread adoption of metaphysical views within the movement, here termed "transcendental homeopathy". Long before the birth of bacteriotherapy ... homeopathic physicians carried out investigation in their own way, and discovered similar medicines, and effected numerous cures ... Hydrophobium was proved in 1833 ... 50 years before Pasteur ... many others followed. 1